A Practical Method for Regioselective 5′-O-tert-Butyldimethylsilyl Deprotection of Persilylated Nucleosides by Methanolic Phosphomolybdic Acid - Huang, Hua-Shan; Kong, Rui; Zheng, Xiu-An; Chen, Wei-Jie; Han, Shuai-Bo; Zeng, De-Yun; Gong, Shan-Shan; Sun, Qi (Synlett, 2018)
In nucleoside/nucleotide chemistry, the regioselective cleavage of 5′-O-TBS groups of persilylated nucleosides is a desired approach for structural functionalization at the 5′-position. However, efficient and practical methods for this purpose are still limited. In our research, we found that homogeneous methanolic phosphomolybdic acid (PMA) efficiently catalyzes the regioselective deprotection of 5′-O-TBS groups of a diversity of persilylated nucleoside substrates and can be applied in practical synthesis at scales of up to 15 g. 31P NMR results indicated that an anion cluster forms and the Lewis acidity of homogeneous PMA is organic-solvent dependent. The efficacy and pronounced regioselectivity of methanolic PMA occurs as a result of a lowering of the Lewis acid strength upon solvation of the molybdophosphate anions.
Keywords: deprotection; nucleosides; regioselectivity; desilylation; phosphomolybdic acid; butyldimethylsilyl group